Golpes de Tarantino: cinema, história e Deleuze para uma crítica especializada - Queiroz, Filipe Artur de Sousa (2024)
Depth of field is one of the instruments of cinematographic narrative that explains the existence of layers of interpretations of time, in the past, present and future. The location and articulation of these layers is one of the tasks of the theory of history. This is a thesis about depth of field in reflecting on the tension between historical and cinematic narrative. Seeking to explore the potential of historical narrative, more specifically its theoretical-historical dimension, this work assumes theory as a relevant component for the production of historical knowledge. By choosing the historical narrative as an object of reflection, the medium chosen for this endeavor is the cinematographic narrative, with a special focus on the work of Quentin Tarantino. The method adopted to link these two domains lies in examining the relationship between cinema and history. From this starting point, the central problem emerges: the tension between visual narrative (cinema) and historical narrative (history). To adequately address this issue, a specialized critique was developed that explores the intersection of these two operations, based on the image typology derived from Gilles Deleuze's cinematic semiotics.